Codes over F4 + vF4 and some DNA applications - Bayram, Aysegul; Oztas, Elif Segah; Siap, Irfan (SPRINGER, 2016)
In this work, we study the structure of linear, constacyclic and cyclic codes over the ring R = F-4[v]/(v(2) - v) and establish relations to codes over F-4 by defining a Gray map between R and F-4(2) where F-4 is the field with 4 elements. Constacyclic codes over R are shown to be principal ideals. Further, we study skew constacyclic codes over R. The structure of all skew constacyclic codes is completely determined. Furthermore, we introduce reversible codes which provide a rich source for DNA codes. We conclude the paper by obtaining some DNA codes over R that attain the Griesmer bound.
Keywords: Non-chain rings; Linear codes; Constacyclic codes; Skew codes; DNA codes; SKEW CONSTACYCLIC CODES; CYCLIC CODES; CONSTRUCTION; Computer Science; Mathematics